Implementasi Sistem Inventori, Keuangan, dan SOP sebagai Solusi Permasalahan Internal UMKM ENEF Apparel: Pengabdian - Ali Jamaludin; Muhamad Japar Sidiq; Ratu Badria Lenggang Nagara; Ziyad Rizky Al-Barokah (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
The Community Practice/Field Work Program (KPB-PKL) is an academic initiative designed to provide students with hands-on experience in applying theoretical knowledge in real-world work settings. This program was conducted at ENEF Apparel, Purwakarta, aiming to assist the business partner in improving internal management. The problems identified include disorganized raw material stock management, unsystematic financial reporting, and the absence of clear Standard Operating Procedures (SOP) in the production process. In this program, students actively assisted the partner by developing a more efficient raw material stock management system, preparing simple financial reports based on basic accounting principles, and creating production SOPs to enhance the effectiveness and consistency of work processes. This activity not only provides practical benefits for the SME in improving its management quality but also enriches students’ experience in applying the knowledge gained during their academic studies. Thus, KPB-PKL serves as a platform for developing students’ competencies while contributing directly to the partner business in optimizing operational performance and productivity. The program emphasizes the importance of collaboration between academia and industry in preparing students to face professional challenges.